Different Contexts of Sexual Abuse With a Special Focus on the Context of Christian Institutions: Results From the General Population in Germany - Witt, Andreas (Journal of interpersonal violence, 2022)
Recent revelations of the extent of sexual abuse in the Roman Catholic Church in Germany and the United States have once more triggered the debate about sexual abuse. Those inquiries identify cases that are known to authorities or have been recorded in these institutions. However, to assess the full magnitude of the problem, data beyond recorded or known cases are needed, as it can be assumed that a vast number of cases are not reported and are hence not included in such file reviews. Therefore, representative surveys are needed. The aim of the present study was to examine the prevalence of sexual abuse by priests and in different contexts in the German population based on a representative sample. A total of 2,510 participants (54.3% female, M = 48 years) were retrospectively asked about different experiences, offenders, contexts, and so on, of child sexual abuse using questions that were used to assess child sexual abuse in prior surveys and the Childhood Trauma Questionnaire (CTQ). In sum, 0.21% (n = 7) of the participants reported child sexual abuse by a priest or pastor. 0.16% reported child sexual abuse in an institution of the Roman Catholic Church. Results also indicated that victims of sexual abuse by priests and pastors reported rather severe types of sexual abuse based on the CTQ in comparison with other contexts, such as schools. Extrapolating the data for the population, it can be assumed that the estimated number of victims is much higher than those identified by research based on recorded cases.